Face Recognition using Symbolic Data with Texture Features - Naik, Yogish G.R; Kumar, Arun H.D; Prabhakar, C.J (International Journal of Computer Sciences and Engineering, 2025)
Face recognition is a type of biometric identification method, it is challenging and one of the active research area in the field of Computer Vision. Variations in face image is due to changes in expression, presence of occlusion, geographical variations and illumination along with aging are some of the challenges to face recognition technique. In this paper, we attempt to solve illumination challenge for face recognition. Here, we propose a novel symbolic face recognition technique using Logarithm Gradient Histogram (LGH). Experimental results are carried out on standard benchmark databases like Extended YaleB, ORL. The performance of the proposed face recognition technique turns out to be 94.35 to 100% for the mentioned databases